Utility of a perioperative nutritional intervention on postoperative outcomes in high-risk head & neck cancer patients. (March 2016) - Rowan, Nicholas R.; Johnson, Jonas T.; Fratangelo, Christina E.; Smith, Brenda K.; Kemerer, Patricia A.; Ferris, Robert L.
Highlights: Arginine-enhanced formulas may improve post-operative outcomes. We compared nutrition supplementation in high-risk head and neck surgical patients. Enhanced nutrition is associated with decreased length of stay and fistula formation. Perioperative immunonutrition may improve clinical outcomes and healthcare savings. Summary: Objectives: Investigate both the utility and feasibility of perioperative nutritional supplementation with an arginine-enriched immunonutrition formula to high-risk head and neck cancer surgical patients and examine its effects on acute post-operative clinical outcomes. Materials & Methods: This prospective, non-randomized, interventional cohort study compared high-risk head and neck cancer surgical patients who consumed a pre- and post-operative arginine-based nutritional supplement to those that did not. Outcome measures included post-operative complications, length of hospitalization, readmission rates and measurement of nutritional biomarkers. Results: 195 high-risk head and neck cancer surgical patients were enrolled. 59% of the patients used the nutritional supplement, 41% did not. Of the 80 patients who did not receive the immunonutrition formula, 38 (47.5%) experienced post-operative complications of all types as compared to 29 of the 115 (25.2%) patients who did consume the product ( p  = 0.0021). Pharyngeal leaks or fistulas were the most common post-operative complications in both groups and more common in patients who did not receive supplementation ( p  = 0.007). Length of stay was on average 2.8 days longer in patients who did not have enhanced nutrition ( p  = 0.02), while readmission rates between the two groups were similar ( p  = 0.91). Measurements of nutritional biomarkers were not reported secondary to low collection rates. Conclusion: Enhanced perioperative nutrition may result in significant reductions of post-operative fistula formations and decreased length of stay in a high-risk head and neck cancer population, even in the setting of poor compliance. The potential quality improvement in both patient care and healthcare cost is both real and significant.